2023
DOI: 10.1647/20-00056
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Clinical, Cytological, and Histopathological Features Associated with Neoplasms in Captive Avian Species in Melbourne, Australia

Michelle Sutherland,
Kathy Luk,
Natalie Courtman
et al.

Abstract: Over a 3.5-year period, tissue samples from 141 companion and aviary birds with clinically suspected, naturally occurring solid neoplasms were collected via surgical biopsy (n = 53) or at necropsy examination (n = 88) from a population of birds presenting to an avian veterinary clinic in Melbourne, Australia. Neoplastic processes were identified in 73.7% (n = 104) of samples, with 83.7% (n = 87) being interpreted as malignant neoplasia and 16.3% (n = 17) being interpreted as benign neoplasia. The overall estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Previous investigations have shown varying rates of neoplastic involvement in different organs and systems. A study of 141 solid neoplastic lesions of pet and aviary birds revealed higher incidences of neoplasms in the gastrointestinal and reproductive systems (Sutherland et al., 2023 ). In a pathological study of 827 tissue samples obtained from various avian species, neoplasia was diagnosed in 9.2% of birds, with the majority (79%) being diagnosed as malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations have shown varying rates of neoplastic involvement in different organs and systems. A study of 141 solid neoplastic lesions of pet and aviary birds revealed higher incidences of neoplasms in the gastrointestinal and reproductive systems (Sutherland et al., 2023 ). In a pathological study of 827 tissue samples obtained from various avian species, neoplasia was diagnosed in 9.2% of birds, with the majority (79%) being diagnosed as malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Coeliotomy and surgical excision are accepted as routine treatments for intracoelomic neoplasms (Filippich, 2004 ). Various neoplasms have been diagnosed in pet and aviary birds affecting different organ systems (Nemeth et al., 2016 ; Robat et al., 2017 ; Sutherland et al., 2023 ). Leiomyosarcoma (LMS) is a malignant neoplasm of smooth muscle origin and is the most common sarcoma affecting the uterine tissue in humans (Verta et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%